Neural and self-reported responses to antisocial news stories: Entertaining versus traditional news introduction. (January 2022) - Kim, Shin Ah; Kim, Sang Hee; Hamann, Stephan
Abstract: Recently, as entertainment programs have become more prevalent in the news media, there is a growing need to understand how entertainment appeal influences viewers' sociomoral evaluation of news content. We investigated neural and self-reported moral evaluation of antisocial news content in college students who viewed real-life news reports featuring moral violations inside a functional magnetic resonance imaging (fMRI) brain scanner. Each news report was preceded by a traditional or entertaining style of introduction. The behavioral results showed that antisocial severity was reduced for antisocial news content that was presented following entertaining news introductions versus traditional news introductions. The fMRI results showed that entertainment news introductions tax more cognitive control resources than traditional news introductions during news processing, as indicated by greater activation in the dorsolateral prefrontal region; however, they diminish moral saliency, as suggested by the reduced activation in the medial prefrontal region. We also found that greater dorsolateral prefrontal activation during the early phase of news reports was associated with more lenient moral acceptability ratings in the entertainment condition. Furthermore, reduced functional connectivity of the mentalizing brain network was observed in the entertainment condition when compared with the traditional condition. These results suggest that entertainment appeal may increase resource depletion, diminish moral sensitivity, and reduce functional integration of relevant social information during news processing, thus hindering viewers' moral scrutiny. This novel study contributes to a better understanding of how entertainment features influence viewers' sociomoral evaluation of news stories. Highlights: Neural and self-reported moral evaluations of antisocial news stories following entertaining introduction were evaluated. Antisocial severity was reduced for antisocial content following entertaining vs traditional news introductions. Entertaining introduction indicated neural signs of taxing more cognitive control resources and diminishing moral saliency. Entertaining vs traditional introduction showed reduced functional connectivity of the mentalizing brain network. Results contribute to a better understanding of how entertainment features influence sociomoral evaluation of news stories.